2022
DOI: 10.1111/jdv.18352
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy of skin parasitoses, bites and stings: a systematic review of the literature

Abstract: Besides classic applications, dermoscopy has gained significant appreciation also for non‐tumoral dermatoses (general dermatology). In this field, skin parasitoses (infestations), bites and stings have been reported among the conditions that may benefit most from dermoscopic examination. However, published data on this topic are sparse and often lack a standardized analytical approach. In this systematic review of the literature, we sought to summarize available data on dermoscopy of cutaneous parasitoses, bit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 152 publications
(418 reference statements)
0
12
0
Order By: Relevance
“…The present systematic review highlights that there is a large body of literature when it comes to dermoscopy of nonparasitic skin infections, with a higher number of bacterial and fungal dermatoses having at least one description compared with viral diseases. Of note, while articles published on dermoscopy of skin parasitoses, bites, and stings are mainly single case reports or small case series [ 166 ], several larger studies are available in the field of nonparasitic infectious dermatoses, likely because they are more common than the former group of conditions. However, level of evidence analysis showed that most of the published articles are of poor quality with a lack of comparative cohort, gold-standard diagnostic reference, blinding, and/or consecutive recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present systematic review highlights that there is a large body of literature when it comes to dermoscopy of nonparasitic skin infections, with a higher number of bacterial and fungal dermatoses having at least one description compared with viral diseases. Of note, while articles published on dermoscopy of skin parasitoses, bites, and stings are mainly single case reports or small case series [ 166 ], several larger studies are available in the field of nonparasitic infectious dermatoses, likely because they are more common than the former group of conditions. However, level of evidence analysis showed that most of the published articles are of poor quality with a lack of comparative cohort, gold-standard diagnostic reference, blinding, and/or consecutive recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…However, level of evidence analysis showed that most of the published articles are of poor quality with a lack of comparative cohort, gold-standard diagnostic reference, blinding, and/or consecutive recruitment. Additionally, as previously reported for skin parasitoses, bites, and stings [ 166 ], dermoscopic terminology used in published articles on bacterial, viral, and fungal dermatoses is highly variable (even for the same condition), thus generating confusion for use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 During larval stage, the mite may infest humans as accidental hosts, with a greater activity from May to October. 3 Chiggers pierce the host's skin and feed on tissue fluid and bloods, through the formation of a stylostom (a small feeding hollow tube penetrating the epidermis) that causes epidermal enzymatic lysis with a consequent local skin inflammatory response. 1 LC-OCT allowed to identify microscopic details indicative of the stylostome as a hyperreflective round structure overlying a hyporeflective cone-shaped shadow, corresponding to epidermal destruction (Figure 2B).…”
mentioning
confidence: 99%
“…scopy has demonstrated to be a helpful method for diagnosis and treatment monitoring of parasitic and infectious disorders (hence the term entomodermoscopy was coined). 2,3 Line-field confocal optical coherence tomography (LC-OCT) is a newly introduced in-vivo technique for the study of skin changes in neoplastic and inflammatory diseases, recently applied also for the identification of Sarcoptes scabiei infestation. 4,5 Herein we describe a case of 32-year-old pregnant woman referred to our attention for an intensely itchy skin eruption appeared after participation in a countryside picnic the day before.…”
mentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Dermoscopic features of the entities that may clinically resemble cutaneous mastocytosis. References [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%